2017
DOI: 10.2147/jpr.s142896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxycodone patient-controlled intravenous analgesia after cesarean section: a randomized controlled study

Abstract: BackgroundOxycodone is a semisynthetic μ-opioid receptor agonist with a potentially good analgesic efficacy in visceral pain. This study aims to compare the efficacy of oxycodone with sufentanil patient-controlled intravenous analgesia (PCIA).MethodsOne hundred and twenty primiparas undergoing elective cesarean section were randomized into four groups by different drugs of PCIA: group S (sufentanil 100 μg), group OS1 (sufentanil 70 μg, oxycodone 30 mg), group OS2 (sufentanil 50 μg, oxycodone 50 mg), and group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…In conclusion, for clinical purposes, oxycodone or morphine can be used as first-line i. Total dose of study drug (mg) 22 19 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] 0.048…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, for clinical purposes, oxycodone or morphine can be used as first-line i. Total dose of study drug (mg) 22 19 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] 0.048…”
Section: Resultsmentioning
confidence: 99%
“…This rate appeared to be low but probably related to the systematic prevention of nausea used in this study (see method). With oxycodone, the incidence of PONV in the literature vary according to doserelated studies and route of administration (p.o., i.v., s.c…) [15][16][17][18][19]23]. In fact, no study appears to ultimately demonstrate superiority to oxycodone vs morphine.…”
Section: Pca Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…The paradigm of prenatal opioid exposure, whether the opioid is morphine, buprenorphine, or oxycodone, etc., is well established in the literature. Oxycodone as a postoperative analgesic has been reported in the literature for postpartum pain or caesarian sections in lieu of morphine drips [26,27]. The PNO group is representative of the human scenario in which a mother undergoes a caesarean section and is prescribed oxycodone for postpartum pain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that per os oxycodone was associated with better pain control, less serious opioid-related adverse events (ORAEs) and a faster onset of action due to a better pharmacokinetic profile: higher oral bioavailability and lower plasma variability [15][16][17][18][19]. However, controversies have arisen as a result of recent clinical studies and meta-analysis that have shown that per os oxycodone did not reduce adverse events and pain relief.…”
mentioning
confidence: 99%